Stable passively Q-switched 1537 nm Er:Yb:Lu2Si2O7 pulse microlaser with peak output power higher than 10 kW at 1–2 kHz. (November 2022) - Chen, Yujin; Huang, Jianhua; Lin, Yanfu; Gong, Xinghong; Luo, Zundu; Huang, Yidong
Highlights: Compact and stable passively Q -switched Er:Yb:Lu2 Si2 O7 pulse laser was developed. 1537 nm pulse laser with peak power higher than 10.0 kW at 1–2 kHz was realized. Er:Yb:Lu2 Si2 O7 crystal is a high-energy pulse laser gain medium at kilohertz level. Abstract: Compact and stable passively Q -switched 1537 nm pulse microlasers operating at 1–2 kHz were developed based on Er:Yb:Lu2 Si2 O7 crystal. A stable 1537 nm pulse microlaser with single pulse energy of 33.0 μJ, width of 3.0 ns, repetition frequency of 1.0 kHz, and peak output power of 11.0 kW was realized, when the crystal was end-pumped by a 975.6 nm pulsed laser diode with pulse width of 0.3 ms and period of 1.0 ms. When the pump pulse period of the LD was changed to 0.5 ms, the repetition frequency of the output pulse laser increased to 2.0 kHz and the peak output power was still higher than 10.0 kW. The results show that the Er:Yb:Lu2 Si2 O7 crystal is an excellent gain medium for high-energy eye-safe pulse laser operating at kilohertz level.